South African midwife specialists' experiences in the utilisation of their knowledge and skills - Kagiso P. Tukisi; Zelda Janse van Rensburg; Wanda Jacobs (AOSIS, 2024)
Background: Midwifery specialisation was introduced in 1993 as a response to escalating maternal and neonatal mortalities and shortage of physicians in rural parts of South Africa. Basic midwives enrolled into a postgraduate midwifery qualification to extend their knowledge and skills which enabled them to manage complicated obstetric conditions. The postgraduate midwifery qualification rendered them midwife specialists upon completion of the course. Yet, MS remain underutilised in clinical facilities due to limiting practice regulations and fear of medico-legal litigations, leading to forfeiture of skills. Aim: The study aimed to explore and describe midwife specialist' experiences of optimal utilisation of their knowledge and skills in public health facilities in South Africa. Setting: Public health facilities based in seven provinces in South Africa where MS were employed, formed part of the research setting. Methods: A qualitative, descriptive and explorative research design was followed using phenomenological approach. Sixteen purposefully sampled midwife specialists participated in four focus group interviews. Data were analysed using Collaizi's descriptive method. Findings: Three themes, each with categories, were derived from the data. Research results confirmed midwife specialist' limited utilisation of knowledge and skills in public facilities. This was associated with the existing practice regulations, restricting midwife specialists to basic midwifery roles. Conclusion: The lack of practice regulations, particularly for midwife specialists hinders optimal utilisation of their knowledge and skills in the public health facilities. Contribution: This study highlighted midwife specialist' barriers in optimally embracing their expert knowledge and skills. Barriers may guide formulation of strategies to facilitate midwife specialist' knowledge and skills utilisation.